2019
DOI: 10.29333/ejmste/109236
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Style Differences between Male and Female Science Teachers in Qatari Schools: Possible Impact on Student Achievement

Abstract: In Qatar's gender-segregated public schools, female students outperform male students in international science tests such as PISA and TIMMS. In contrast to the international trend for top performing countries, however, female students report lower levels of interest in science-based careers than males. One possible factor that may contribute to this discrepancy is the difference in teaching styles between female teachers and their male counterparts. In this paper we focus on results obtained from 105 classroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…Available research demonstrates that non-Qatari students outperform Qataris, as is evidenced in a recent and past study by Ali et al, (2022), and El-Emadi et al, (2019) [45,46], causing a loss to the country's economic and social capital [47]. Similarly, student enrollment at Qatar University (QU), the only and most prominent national university in Qatar, tells a similar story.…”
Section: Discussionmentioning
confidence: 68%
“…Available research demonstrates that non-Qatari students outperform Qataris, as is evidenced in a recent and past study by Ali et al, (2022), and El-Emadi et al, (2019) [45,46], causing a loss to the country's economic and social capital [47]. Similarly, student enrollment at Qatar University (QU), the only and most prominent national university in Qatar, tells a similar story.…”
Section: Discussionmentioning
confidence: 68%
“…The study of El-Emadi et al (2019) found out that female teachers prepared more to create more common classroom discussions by involving students in conversations and bidirectional communication and allowing their students to articulate their opinions and establish a more student-centered learning environment compared to their male counterpart.…”
Section: Resultsmentioning
confidence: 99%
“…In Ecuadorian culture as in other countries, gender differences, beliefs and educational preferences are found, in this order. Ahmad et al, (2019) state that similarities between male and female teachers were found to be important. For the present study, university students in the Province of Chimborazo showed more sympathetic affection when receiving classes or educational guidance from female professors.…”
Section: Discussionmentioning
confidence: 97%